world is not a field: An interview with Michèle Lamont (Sociologisk Forskning, 2019)
In this interview, Michèle Lamont discusses her intellectual trajectory in relation to other sociologists and research fields. The starting point is her relationship to Bourdieu’s field theory in 1980s Paris. She describes how her empirically grounded work developed as a critique of Bourdieu’s oeuvre yet draws heavily on it. A common thread in her work is a focus on social and symbolic boundaries and their relation to evaluation and pluralism, which she has extended from her early studies of class boundaries to empirical and theoretical work, ranging from more general cultural processes of inequality and stigmatization, to knowledge production and evaluation in academia. The importance of cumulative work in sociology and the value of a plurality of criteria of worth across different domains emerge as two central themes in the interview. Finally, Lamont reflects on the current status of the sociology discipline and its role in the public sphere. The interview took place in Lund on 7 March 2018, where Lamont was invited keynote speaker at the Sociologidagarna 2018 conference.
Keywords: Michèle Lamont; Bourdieu; symbolic boundaries; morality; STS; evaluation; sociology profession